2016
DOI: 10.1111/eje.12226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an assessment system for professionalism amongst dental students

Abstract: The assessment programme has good internal reliability and validity and suggests that basing an assessment system around the explicit theoretical model is a valuable educational tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Fourteen studies reported that programmatic assessment generated sufficient information to enable meaningful triangulation and high-stakes, robust decision-making [15,16,18,19,24,25,[29][30][31][32][37][38][39][40]. Arguments for this conclusion involved findings such as high levels of assessors' agreement [24,30,32,37]; the perceived fairness or acceptability by learners and teachers [23,24,30]; satisfactory reliability estimates [15, 23-25, 29, 31, 37]; the coherent nature of the program that ensured all competencies were considered [17, 18, 21, 22, 28-30, 34, 38]; and early detection of struggling learners [15,18,22,24,32,38], specifically of problematic progression on the domains of professionalism and communication, which went undetected prior to implementation [15,24].…”
Section: Theme 1: the Integration Of The Decision-making And Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen studies reported that programmatic assessment generated sufficient information to enable meaningful triangulation and high-stakes, robust decision-making [15,16,18,19,24,25,[29][30][31][32][37][38][39][40]. Arguments for this conclusion involved findings such as high levels of assessors' agreement [24,30,32,37]; the perceived fairness or acceptability by learners and teachers [23,24,30]; satisfactory reliability estimates [15, 23-25, 29, 31, 37]; the coherent nature of the program that ensured all competencies were considered [17, 18, 21, 22, 28-30, 34, 38]; and early detection of struggling learners [15,18,22,24,32,38], specifically of problematic progression on the domains of professionalism and communication, which went undetected prior to implementation [15,24].…”
Section: Theme 1: the Integration Of The Decision-making And Learningmentioning
confidence: 99%
“…The use of multiple assessments lowered the perceived stakes of individual assessments [22,33], guided better recall of past performance and stimulated users to monitor progress over time and focus on trends [16,17,20,21,25,27,28,33,35,38,40], and improved identification of strengths and weaknesses to facilitate tailored learning programs [15,16,18,22,24,27,28,32,33]. The programmatic approach sparked emphasis on direct observation and increased feedback [19-22, 28, 29, 34, 38] and enhanced dialogue on performance progress [20,22,28,29,34,40].…”
Section: Theme 2: the Delicate Interplay Between Quantity And Qualitymentioning
confidence: 99%
“…The results of the present finding are in line with those of Zijlstra-Shaw et al, who stated that the dental professionalism is an essential requirement to practice dentistry that covers both abilities and personal qualities. Therefore, a program of assessment that promotes personal and professional development throughout the undergraduate dental education course is needed ( Zijlstra-Shaw et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Professionalism within dental care has been studied by many researchers . While there is no single, clear, discrete definition of professionalism in dentistry, there are many themes that recur consistently within the descriptions of professionalism.…”
mentioning
confidence: 99%
“…Zijlstra ‐ Shaw et al . also described a conceptual framework of dental professionalism among dental students comprising the following eight domains: understands self; understands others; trustworthiness; ability to relate to context; vocational; altruistic; reliability; and accountability. Eli et al .…”
mentioning
confidence: 99%